2000
DOI: 10.1142/s0219024900000061
|View full text |Cite
|
Sign up to set email alerts
|

Mean-Reverting Stochastic Volatility

Abstract: We present derivative pricing and estimation tools for a class of stochastic volatility models that exploit the observed "bursty" or persistent nature of stock price volatility. An empirical analysis of high-frequency S&P 500 index data con rms that volatility reverts slowly to its mean in comparison to the tick-by-tick uctuations of the index value, but it is fast mean-reverting when looked at over the time scale of a derivative contract many months. This motivates an asymptotic analysis of the partial di ere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
119
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(124 citation statements)
references
References 27 publications
5
119
0
Order By: Relevance
“…Recent work has shown that a path-independent option price, in a stochastic volatility environment, can be approximated by pricing a more complex path dependent option in the usual Black-Scholes framework. The volatility risk is included by an extra continuous path-dependent payout function which has the same form as (2.5) [45,46]. This work suggests that the computational framework presented here might also be used to price path dependent options consistent with the market implied volatility.…”
Section: Discussionmentioning
confidence: 98%
“…Recent work has shown that a path-independent option price, in a stochastic volatility environment, can be approximated by pricing a more complex path dependent option in the usual Black-Scholes framework. The volatility risk is included by an extra continuous path-dependent payout function which has the same form as (2.5) [45,46]. This work suggests that the computational framework presented here might also be used to price path dependent options consistent with the market implied volatility.…”
Section: Discussionmentioning
confidence: 98%
“…maxfd; d 0 g. The relationship H ¼ d þ 1 2 [63] allows to deal with a fBm z H ðtÞ, H ¼ d þ 1 2 in order to fix y, g, z, H such that y þ gf ðtÞ þ zz H ðtÞ (13) has the same self-similarity exponent and the same range of RðtÞ. Whilst the contribution off ðtÞ is due to the local agent interactions, the contribution of z H ðtÞ can be interpreted either like the contribution of noise traders, in the case of uncorrelated signal, or like the presence of fundamentalist traders in the market whether a mean reverting process occurs [22]. This gives an interesting perspective about the level of SOC that can be masked by either noise or fundamentalists traders.…”
Section: Discussionmentioning
confidence: 99%
“…Microeconomic models of financial markets rank in complexity from the simplest models, typically considering the interaction of two main types of agents-the fundamentalists and the chartists [18][19][20][21] either without market information or not caring about the fundamentals, thus creating white noise, while mean reversion effects [22] can be accounted due to the activity of fundamentalists. The first question to be raised is whether a microeconomic approach can be found based on insight about the mechanism of the formation of financial quantities.…”
Section: Introductionmentioning
confidence: 99%
“…We plan to address this problem using a systematic statistical analysis in a subsequent article. For now, the reader is directed to current work in (Fouque et al, 2000b), (Nielsen and Vestergaard, 2000) or (Bollerslev and Zhou, 2002).…”
Section: Estimating the Filtered Stochastic Volatility Distributionmentioning
confidence: 99%